The Level of Program Learning Outcomes (PLOs) achievements among the Interns and Fresh graduates of the BDS program - Muhammad Shoaib Ahmedani; AlBandary Hassan AlJameel; Mamdouh Hamithy; Feras Al.Zahrani; Anas Bin Dahmash; Mohammed Al.Thuniyan; Syed Rashid Habib (Elsevier, 2020)
Objectives: Success of Dental Program depends on the students' performance measured in terms of Program Learning Outcomes (PLOs) achievement. The present study was carried out to evaluate the level of achievement of the PLOs among dental interns and fresh graduates as a direct measure for the success of the BDS program of the College of Dentistry, King Saud University. Methods: An online survey instrument was used to seek the opinion of male and female dental interns and fresh graduates about the attainment of the PLOs distributed over 6 domains: patients' care, communication & interpersonal skills, professionalism, practice management, information management & critical thinking, and health promotion domains on a five-point Likert scale. The data were analyzed using Minitab Statistical Software version 15.1.31.0. Descriptive as well as Chi-Square statistics were calculated to determine the significance of the responses to the levels of PLOs achievement at 0.05 level of significance. Results: Levels of achievement of PLOs under the 6 domains indicated a good standard of planning, delivery, and evaluation of the BDS program. On an overall average score basis, the achievement of PLOs under the Communication-Interpersonal Skills domain ranked as highest with a score of 4.22 ± 0.88 followed by Professionalism (4.18 ± 0.85), Practice Management (4.03 ± 0.93), Patient care (3.94 ± 0.84) and Information Management-Critical Thinking domain with a score of 3.68 ± 0.96. The lowest score was achieved under Health promotion domain with a score of 3.60 ± 0.93. Statistically, no significant differences were found based on the graduation years and gender of the respondents. Conclusion: The study revealed significant achievement of PLOs under all learning domains of the BDS curriculum taught at the College of Dentistry, King Saud University. However, achievement scores for Information Management, Critical Thinking, and Health Promotion domains require further improvement through reinforcement of the curriculum, updating of content, and teaching strategies.